2020
DOI: 10.1177/1538574420939356
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Body Mass Index and Perioperative Mortality After Repair of Ruptured Abdominal Aortic Aneurysms

Abstract: Objective: The attempt to repair a ruptured abdominal aortic aneurysm carries a significant risk of perioperative mortality. The relationship between body mass index (BMI) and outcomes after repair of ruptured abdominal aortic aneurysms (AAAs) has not been well defined. We report the association of BMI with outcomes after ruptured AAA repair. Methods: Patients undergoing ruptured AAA repairs between 2008 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…We used a ubiquitously used model, relevant to clinical findings that obesity and hypertension increase the risk of mortality in AA and AAD. 58,59 The results (Figures 1, 2 and Figure S1) confirmed that AngII/AT1R interaction in the context of ApoE −/− genotype and high-fat diet together create the AA and AAD disease state. Therefore, TRV027 and OLM were tested in this model for efficacy to prevent the disease.…”
Section: Discussionsupporting
confidence: 58%
“…We used a ubiquitously used model, relevant to clinical findings that obesity and hypertension increase the risk of mortality in AA and AAD. 58,59 The results (Figures 1, 2 and Figure S1) confirmed that AngII/AT1R interaction in the context of ApoE −/− genotype and high-fat diet together create the AA and AAD disease state. Therefore, TRV027 and OLM were tested in this model for efficacy to prevent the disease.…”
Section: Discussionsupporting
confidence: 58%
“…There were 28 studies 70,96,107,109,150,156,160–181 (29 cohorts; 2,068,365 participants) with surgical populations (Table S3): 17 cohorts in North America, 6 were in Europe, 4 in East Asia, and 1 each in South Asian and the Pacific. Mean age of participants ranged from 46 to 83 years.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study involving 5,455 AAA patients revealed that morbidly obese individuals (BMI>34 kg/m 2 ) exhibited higher 30-day mortality rates in both open aneurysm repair (OAR) and endovascular aneurysm repair (EVAR) procedures compared to non-obese patients, including those with milder obesity ( 24 ). Additionally, for every 1 kg/m2 increase in BMI, the risk of 30-day death in hospitalized patients undergoing repair for ruptured abdominal aortic aneurysm was significantly elevated by 1.08 (95% CI,1.01-1.17; P=0.04) ( 23 ).…”
Section: Obesity To Aaa: Foe or Friend?mentioning
confidence: 99%